Can the choice of eco-design principles affect products' success?. (2019) - Maccioni, Lorenzo; Borgianni, Yuri; Pigosso, Daniela C. A.
Abstract : Despite the potential to lead to enhanced environmental performance, the extent to which eco-design leads to success is still unclear. In order to lay bare the effects of eco-design implementation, this paper focuses on understanding the correlations between specific eco-design principles and success through an exploratory study. A sample of 178 products, characterized in terms of their success levels and implemented eco-design principles, was statistically analyzed. The results indicate a number of positive correlations for principles that tend to favor success (e.g. intensified use and product/service systems) and negative correlations for principles that tend to moderate the chances of success (e.g. minimize packaging). Although the mechanisms that cause this phenomenon should be further investigated, the findings can provide designers with additional recommendations for the selection of eco-design principles.